"Endocytic pH regulates cell surface localization of glycolipid antigen loaded CD1d complexes". (January 2016) - Arora, Pooja; Kharkwal, Shalu S.; Ng, Tony W.; Kunnath-Velayudhan, Shajo; Saini, Neeraj K.; Johndrow, Christopher T.; Chang, Young-tae; Besra, Gurdyal S.; Porcelli, Steven A.
Graphical abstract: Highlights: Neutralization of endosomal pH increases presentation of Th2-biasing αGC analogues, and their association with CD1d in cholesterol rich "lipid raft" microdomains. Pulsing the antigen presenting cells with αGC Th2-agonist in the presence of chloroquine induces higher NK cell transactivation. Abstract: Invariant natural killer T (iNKT) cells recognize glycolipid antigens presented by CD1d, an antigen presenting protein structurally similar to MHC class I. Stimulation of iNKT cells by glycolipid antigens can induce strong immune responses in vivo, with rapid production of a wide variety of cytokines including those classically associated with either T helper type 1 (Th1) or type 2 (Th2) responses. Alterations in the lipid tails or other portions of CD1d-presented glycolipid ligands can bias the iNKT response towards production of predominantly Th1 or Th2 associated cytokines. However, the mechanism accounting for this structure-activity relationship remains controversial. The Th1-biasing glycolipids have been found to consistently form complexes with CD1d that preferentially localize to plasma membrane cholesterol rich microdomains (lipid rafts), whereas CD1d complexes formed with Th2-biasing ligands are excluded from these microdomains. Here we show that neutralization of endosomal pH enhanced localization of CD1d complexes containing Th2-biasing glycolipids to plasma membrane lipid rafts of antigen presenting cells (APC). Transfer of APCs presenting these "stabilized" CD1d/αGC complexes into mice resulted in immune responses with a more prominent Th1-like bias, characterized by increased NK cell transactivation and interferon-γ production. These findings support a model in which low endosomal pH controls stability and lipid raft localization of CD1d-glycolipid complexes to regulate the outcome of iNKT cell mediated responses.